2014
DOI: 10.1371/journal.pone.0098692
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Dopamine Measurement in Awake Monkeys

Abstract: Fast-scan cyclic voltammetry (FSCV) is often used to measure real-time dopamine (DA) concentrations in awake, behaving rodents. Extending this technique to work in monkeys would provide a platform for advanced behavioral studies and a primate model for preclinical research. The present study demonstrates the feasibility of DA recordings in two awake monkeys (Macaca mulatta) using a mixture of techniques adapted from rodent, primate and brain slice work. We developed a long carbon fiber electrode to operate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 48 publications
(82 reference statements)
2
47
1
Order By: Relevance
“…However, local terminal stimulation, a technique regularly used in brain-slice studies, elicited dopamine release in 10 out of 14 attempts and facilitated the recording of dopamine release during an unexpected juice reward. Thus, in agreement with our published work in monkeys, Schluter et al (144) concluded that dopamine release is more difficult to detect in the primate brain than in rodents.…”
Section: Novel Applicationssupporting
confidence: 91%
See 1 more Smart Citation
“…However, local terminal stimulation, a technique regularly used in brain-slice studies, elicited dopamine release in 10 out of 14 attempts and facilitated the recording of dopamine release during an unexpected juice reward. Thus, in agreement with our published work in monkeys, Schluter et al (144) concluded that dopamine release is more difficult to detect in the primate brain than in rodents.…”
Section: Novel Applicationssupporting
confidence: 91%
“…A more recent FSCV study by Schluter and coworkers (144) explored the use of electrical stimulation to evoke dopamine release in the rhesus striatum. Electrical stimulation of midbrain dopamine neurons in the substantia nigra/ventral tegmental area (SN/VTA) is widely used in rodent studies as an aid in electrode positioning and to study the regulation of dopamine overflow.…”
Section: Novel Applicationsmentioning
confidence: 99%
“…CFM sensors have realized prevalent implementation in analyzing the mechanisms of dopamine signaling and its function in our everyday behavior and in pathology 10,1719 . Considerable studies have further attempted to investigate the spatial diversity of dopamine neurotransmission in the striatum using the CFM sensor 3,4,17,20,21 . These single channel investigations, however, are limited by the inability to reproduce precisely dopamine measurements at specific brain sites, as they require serial repositioning of the sensor and/or impractical numbers of specimens to assess dopamine heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent review papers are available which thoroughly describe how the approach has been used in awake and behaving rats (Stamford, 1990; Phillips et al, 2003a; Robinson et al, 2003). The technique has also been used in other species including Drosophila (Vickrey et al, 2009), lamprey (Ryczko et al, 2013), mice (Parker et al, 2010; Natori et al, 2009; Ehrich et al, 2014), monkeys (Ariansen et al, 2012; Schluter et al, 2014), and humans (Kishida et al, 2011). …”
Section: Introductionmentioning
confidence: 99%